Laju Pertumbuhan Dan Kecepatan Molting Kepiting Bakau (Scylla serrata) Dengan Pemberian Ekstrak Daun Pakis Hutan (Diplazium caudatum) - Achmad Romadhon; Eva Prasetiyono; Arthur Muhammad Farhaby (Journal of Tropical Marine Science, 2022)
The cultivation of mud crabs is growing to get crabs in the soft shell condition. But most of the soft shell crab's farmers do not experience sustainable business. The main obstacle is the length of the maintenance period and moulting time does not unison thereby causing the feed and operating costs to be high. The research aimed to examine the effect of injection with forest fern leaf extract on growth rate and moulting speed of mangrove crabs (Scylla serrata) and determine the best dose in the process of injecting forest Fern Leaf extract for mangrove crab (Scylla serrata). Treatment of mangrove crab (Scylla serrata) weight ± 100 g with dose: P1 (NaCL 0.9%) P2 (50 mg.L-1) P3 (75 mg.L-1) P4 (100 mg.L-1) P5 (125 mg.L-1) 5 crabs each are cared for 30 days, The research was conducted using a single complete random draft (RAL), the results of various analyses showed the significant forest fern leaf extract against the growth of absolute weights, the rate of Specific growth, and relative growth, but no noticeable effect for molting speed and absolute length growth. The results of this research showed that a dose of 125 mg.L-1produces the highest value with result for moulting speed of 0.50 ± 0.57, length absolute growth of 0.37 ± 0.1 weighted absolute growth of 20 ± 5,74, specific growth rate of 0.54 ± 0.13, and relative growth of 0.64 ± 0.18.